Model Optimasi Pola Tanam Polikultur di Daerah Irigasi KAJAR 2C Kota Malang - Kinasih, Mentari; Wirosoedarmo, Ruslan; Suharto, Bambang (Jurnal Pertanian Terpadu, 2018)
The 21.61 Ha of Irrigation area (IA) Kajar 2C is technical irrigation network located in Malang City. This research aims to develop the local commodity, there are rice, corn, cassava, and peanut. The Optimation method used linear programming by solver. The optimation cropping pattern scenario consists of 3 alternative, there are: (1) Rice/Rice/Rice; (2) Rice/Rice/Corn-Peanut; and (3) Cassava-Peanut/Cor/Corn. Every scenario is simulated by cropping patterns alternative by changing planting schedules existing from Oktober I, Oktober II, and Oktober III. Based on the results, the highest profits for each cropping pattern is X5 cropping pattern 7,203 Ha; X6 cropping pattern 10,78 Ha; and X8 cropping pattern 3,627 Ha. The maximum profit is Rp. 146.888.280.